The Nature of Childhood : An Environmental History of Growing Up in America since 1865 - RineyKehrberg, Pamela (Book collections on Project MUSE., 2014)
"Today's organized efforts to lure children outdoors to green spaces signal growing concerns about American youths' deepening estrangement from nature. Covering the last century and a half, this environmental history of American childhood explains how and why we've come to this pass by focusing on those factors that shaped the conflict over who would control children's access to their preferred environments, with adults prevailing more often than not. Armed with technology, however, today's homebound youngsters seemingly are now where they want to be, prompting their elders increasingly to question the wisdom of their protective regime"--